UNSUR INTRINSIK DALAM FILM BLUE SPRING RIDE KARYA SUTRADARA TAKAHIRO MIKI - Anita Sari Ade; Anak Agung Ayu Dian Andriyani; Betty Debora Aritonang (SPHOTA: Jurnal Linguistik dan Sastra, 2020)
Film Blue Spring Ride have flow in which the stiry of the past the main character related to the stiry now that cause change stance in the main character. This study aims to describe the intrinsic elements and moral messages contained in the film Blue Spring Ride by Takahiro Miki. In this study, examining the intrinsic elements, namely the theme, plot, characterization, and background contained in the Blue Spring Ride film with the structuralism theory put forward by Nurgiantoro. This study uses the observation method in data collection, namely the observation and note technique. The data analysis technique used a qualitative descriptive method. Presentation of the results of data analysis uses informal methods. The results of this study indicate that there is a time setting and a place setting, the theme is to tell the life of teenagers who are looking for love. The flow contained in the Blue Spring 6 Ride film is the mixture flow.